PELATIHAN MEDIA PEMBELAJARAN MULTIMEDIA DENGAN POWERPOINT DAN WONDERSHARE UNTUK PENGEMBANGAN SOFT SKILLS SISWABAGI GURU SD &TK1) - Setiawan, Budi; Purnomo, Endro (WARTA, 2016)
Developmentof soft skills in elementary and kindergarten students can be metthrough alearning model based Multimedia Information Communication Technology (ICT). Training development of multimedia-based instructional media and Information Communication Technology aim stop rovide skills in aking mediaan attractive multimedia learning in a way that isrelativel yeasy. The method applied in this activity is the method of presentation of the introduction of the software includes Microsoft Power Point and Wondershare. Demonstration of the method pengoperasionalisasian program and method of making the practice of instructional media directly by the participants in accord ance with their respective subjects with the use of these programs.